Improving the technical training of rhythmic gymnastic athetes by means of folk-stage dance - Kyzim, P.; Batieieva, N. (Slobozhanskyi herald of science and sport, 2021)
Purpose: to experimentally substantiate the improvement of technical readiness of rhythmic gymnastics athletes aged 10-12 years by means of folk-stage dance.